Efficacy of telemedicine intervention in the self-management of patients with type 2 diabetes: a systematic review and meta-analysis - Liu, Fengzhao; Li, Jixin; Li, Xiangyu; Yang, Zhenyu; Wang, Wenru; Zhao, Lijuan; Wu, Tao; Huang, Chengcheng; Xu, Yunsheng (Frontiers in Public Health, 2024)
Purpose We aimed to report the latest and largest pooled analyses and evidence updates to assess the effectiveness of telemedicine interventions for self-management (DSM) in patients with type 2 diabetes mellitus (T2DM). Methods A systematic literature search was conducted using PubMed, Cochrane, Embase, and Web of Science in December 2023. We included randomized controlled trials (RCTs) of adults (≥18 years of age) diagnosed with T2DM where the intervention was the application of telemedicine. The Cochrane Risk of Bias Assessment was used to evaluate quality. The study’s main outcome indicators were glycosylated hemoglobin (HbA1c) and diabetes self-management (DSM) capacity. Results A total of 17 eligible articles, comprising 20 studies and 1,456 patients (734 in the intervention group and 722 in the control group), were included in the evidence synthesis. The baseline characteristics of both groups were similar in all outcomes. Comprehensive analyses showed post-intervention decreases in HbA1c, 2-h postprandial glucose, systolic and diastolic blood pressure, increases in Diabetes Self- Care activities, DSM competencies based on dietary and medication adherence, and improvements in overall DSM scores, all of which were statistically significant. While no statistically significant differences were observed in body mass index, lipids, and other DSM dimensions. Based on subgroup analyses, app-based experimental interventions targeting under 60 years old populations in Asia and North America were found to be more effective and less heterogeneity in the short term (<6 months of intervention). Conclusion Telemedicine interventions may assist patients with T2DM in enhancing their DSM and improving their HbA1c levels. Clinician can use various telemedicine interventions to enhance DSM in T2DM patients, considering local circumstances. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, CRD42024508522.